Effects of double quenching on fatigue properties of high carbon bearing steel with extra-high purity. (November 2019) - Cao, Zhaoxi; Shi, Zhiyue; Yu, Feng; Sugimoto, Koh-ichi; Cao, Wenquan; Weng, Yuqing
Highlights: Double quenching heat treatment is applied for the microstructure control of the bearing steel of 100Cr6. The rotated bending fatigue test and the rolling contact fatigue test are measured to reveal the double quenching effects on the fatigue properties of the bearing steel of 100Cr6. Both prior austenite grain size and the carbide size are significantly refined, both of which are related to the enhanced rolling contact fatigue life of the double quenched 100Cr6. Abstract: In this study, high carbon bearing steel of GCr15 (100Cr6) is applied to explore the double quenching effects on both rotated bending fatigue strength (RBF-strength) and rolling contact fatigue life (RCF-life). The RBF-strength and RCF-life is about 1000 MPa and 1.1 × 10 7 cycles under a maximum Hertzian stress of 4.5 GPa for the single quenched and tempered specimens but about 1030 MPa and 5.6 × 10 7 cycles for the double quenched and tempered specimens. The enhancement of RBF-strength and RCF-life are attributed to the increased impact toughness due to the refinements of both carbides and prior austenite grain size.